Uncontrolled IL‐17 Production by Intraepithelial Lymphocytes in a Case of non‐IPEX Autoimmune Enteropathy. Issue 7 (July 2016) - Paroni, Moira; Magarotto, Andrea; Tartari, Silvia; Nizzoli, Giulia; Larghi, Paola; Ercoli, Giulia; Gianelli, Umberto; Pagani, Massimiliano; Elli, Luca; Abrignani, Sergio; Conte, Dario; Geginat, Jens; et al.
Abstract : OBJECTIVES: : To provide a functional and phenotypic characterization of immune cells infiltrating small intestinal mucosa during non‐IPEX autoimmune enteropathy (AIE), as to gain insights on the pathogenesis of this clinical condition. METHODS: : Duodenal biopsies from a patient with AIE at baseline and following drug‐induced remission were analyzed by immunohistochemistry, immunofluorescence, and flow cytometry, and results were compared with those obtained from patients with active celiac disease, ileal Crohn's disease and healthy controls. Lamina propria (LP) and intraepithelial (IELs) lymphocytes from AIE and controls were analyzed for mechanisms regulating cytokine production. Foxp3 expression and suppressive functions of LP regulatory T cells (Tregs) were analyzed. RESULTS: : The quantitative deficit of Foxp3 expression in Tregs in AIE associates with unrestrained IL‐17 production by IELs. Interleukin (IL)‐17‐producing IELs were rare in the uninflamed duodenum and in the ileum of Crohn's disease patients, and disappeared upon drug‐induced AIE remission. IL‐17 upregulation in CD4 + IELs and CD4 + LP T cells had different requirements for pro‐inflammatory cytokines. Moreover, transforming growth factor‐β (TGF‐β) selectively enhanced IL‐17 production by CD8 + IELs. Intriguingly, although Foxp3 low Tregs in AIE were poorly suppressive, they could upregulate GARP‐LAP/TGF‐β surface expression and enhanced IL‐17 production selectively by CD8 + IELs. Finally, phosphorylated Smad2/3 was detectable in duodenal CD8 + lymphocytes in active AIE in situ, indicating that they received signals from the TGF‐β receptor in vivo . CONCLUSIONS: : AIE is characterized by the appearance of unconventional IL‐17‐producing IELs, which could be generated locally by pro‐inflammatory cytokines and TGF‐β. These results suggest that Foxp3 + Tregs and Treg‐derived TGF‐β regulate IL‐17 production by IELs in the small intestine and in AIE.